Geo-linguistic Route for Exploring the Role of English Language in Mitigating Tension between Dalits and Non-Dalits in Nepal - Bishwokarma, Babu Ram (ILAM इलम, 2023)
Social stratification in Nepal is based on the Hindu Chaturvarna system which has obnoxiously kept Dalits at the bottom of the hierarchy creating an inhumane discrimination against them. Such discriminatory practice has intensified the likelihood of tension between Dalits and non-dalits. Thus, this qualitative study exploring the role of English language in mitigating the tension between Dalits and non-dalits was carried out as a narrative inquiry. Analyzing the data collected from six Dalit students studying in Bachelor’s level under different streams in the Kathmandu Valley through semi-structured in-depth interviews concluded that English language can play a positive role to mitigate the tension between Dalits and non-dalits.